22. THE PREVALENCE OF OPERATION, MONITORING, MAINTENANCE AND REPAIR OF MEDICAL EQUIPMENT AT THE NATIONAL HOSPITAL OF ENDOCRINOLOGY (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the prevalence of operation, monitoring, maintenance and repair of medical equipment at the National Hospital of Endocrinology. Method: Cross-sectional study combined with retrospective data. Results: 100% of medical equipment has operating logs, user manuals, training, monitoring documents, ensuring safety rules and annual maintenance; 95.5% of devices were in normal use; 90.5% of equipment had a new outer shell; 75.2% of devices were repaired immediately and 69.5% were repaired after 10 days. Conclusion: The operation, monitoring, maintenance and repair of medical equipment at the National Hospital of Endocrinology are quite good and by regulations
Keywords: The National Hospital of Endocrinology, repair, medical equipment, operation, monitoring, maintenance.